Health Psychology in Pandemic Response - Alnaimi, Izzeldeen Abdullah; Yamani, Ibrahim Abdul Jaleel; Alkhatib, Ahed J (Journal of Cultural Analysis and Social Change, 2025)
Because of the COVID-19 pandemic, the world is facing a lot of fear due to deteriorating health. As our social bonds and family ties had broken off due to the national quarantine measures and social distancing, people became emotionally distressed having anxiety, frustration, boredom, denial, anger and post-traumatic stress. The spread of false health information, panic buying and public disorder worsens health risk and emergencies. COVID-19 is an ongoing global crisis. Although it started as a health crisis, several management initiatives have been taken in response. These include health policies, public health steps, closure of institutions and even military action. These include the influence of context on adherence to protective behaviors and the containment of outbreaks. The importance of mental health in crisis like a pandemic. Positive mind science gives us a framework for understanding that wellbeing does not merely mean being free from the disease. It also means flourishing, which is to be emotionally engaged, to have good relationships, to be able to achieve things, and to have a purpose in life. Models, theories, and tools have been developed for the management of psychological wellbeing at the individual or social level, or the community. These multi-level strategies respond to the mental health impact of the pandemic in a comprehensive and inclusive manner. Even though wellbeing in global emergencies is very important, we have not seen a lot of efforts to enhance this. It calls for need of the hour for integrated and proactive mental health measures.